SCHOOL OF MASTER TEACHER (SMT) TRAINING: DEVELOPING TEACHERS’ PEDAGOGIC COMPETENCE - Musfah, Jejen; Erviani, Desita (TARBIYA: Journal of Education in Muslim Society, 2018)
AbstractThis study aimed at analyzing School of Master Teacher (SMT) training in developing teacher's pedagogic competence. This study applied a qualitative approach within the framework of case study research. The data was collected through documentation, observation, and interviews. The results showed that SMT training consisted of lectures, social projects, and Classroom Action Research (CAR). Secondly, the training was able to improve teachers’ pedagogic competence with excellent results. 22 of 33 teachers showed accomplished pedagogic competence. While, 9 teachers performed a very good level of the competence in their instruction, 1 teacher gained a medium level, and only 1 teacher received a poor mark.AbstrakPenelitian ini bertujuan untuk menganalisis pelatihan School of Master Teacher (SMT) dalam mengembangkan kompetensi pedagogik guru. Penelitian ini menerapkan pendekatan kualitatif dalam kerangka penelitian studi kasus. Data dikumpulkan melalui dokumentasi, observasi, dan wawancara. Hasil penelitian menunjukkan bahwa pelatihan SMT terdiri dari ceramah, proyek sosial, dan Penelitian Tindakan Kelas (PTK). Kedua, pelatihan ini mampu meningkatkan kompetensi pedagogik guru dengan hasil yang sangat baik. 22 dari 33 guru menunjukkan kompetensi pedagogik yang baik. Sementara, 9 guru menunjukkan tingkat kompetensi yang sangat baik dalam pengajaran mereka, 1 guru memperoleh tingkat sedang, dan hanya 1 guru yang mendapat nilai buruk. How to Cite : Musfah, J., Erviani, D. (2018).  School of Master Teacher (SMT) Training: Developing Teachers’ Pedagogic Competence. TARBIYA: Journal of Education in Muslim Society, 5(2), 126-134. doi:10.15408/tjems.v5i2.10622.